Gambaran Pengelolaan Limbah Padat Medis Bahan Berbahaya dan Beracun di Rumah Sakit Dr. J.P. Wanane Kabupaten Sorong - Talakua, Febry (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Based on data from the World Health Organization, health service facilities (Fasyankes) produce around 75-90% of domestic waste or what is known as hazardous toxic waste (B3) originating from administrative rooms, kitchens and households. The remaining 10-25% is classified as hazardous waste (B3), including sharp objects and infectious waste.This research aims to determine the description of medical solid waste management for hazardous toxic materials (B3) at the Dr. J.P Wanane Regional General Hospital, Sorong Regency. The type of research is non-experimental quantitative using descriptive studies. The sample consisted of 36 respondents taken from the total population. This research technique uses total sampling with a questionnaire measuring tool. This research was conducted from 14 August to 1 September 2023. The results of this research showed that the majority of B3 solid medical waste management was good, 33 respondents (91.7%), 34 respondents (94.4%), and storage. Transportation 34 respondents (94.4%), Disposal 34 respondents (94.4%). The conclusion of the 4 solid B3 medical waste management variables is that the majority are Good, namely for sorting there are 33 respondents (91.7%), Storage 34 respondents (94.4%), Transportation 34 respondents (94.4%), Disposal 34 respondents (94, 4%). and fulfill the requirements and comply with the regulations set by the J.P Wanane Regional Hospital, Sorong Regency. Suggestion: It is hoped that the hospital will provide education and training to all employees at J.P Wanane Hospital, Sorong Regency regarding the importance of using PPE properly. It is also hoped that the J.P. Wanane Regional Hospital, Sorong Regency, will carry out transport by a third party twice a month to avoid the proliferation of vectors which can cause the spread of unwanted diseases and reduce the aesthetic value due to excessive accumulation of medical waste.Keywords: Sorting, Transportation, Disposal Storage solid B3 waste